Diagnosis and treatment of epidemic myalgia: A review of the literature over the last 10 years (Research, Society and Development, 2023)
Epidemic myalgia, also known as epidemic myositis, is a condition characterized by severe, widespread muscle pain. This condition may be associated with several viruses, such as influenza, Coxsackie, Epstein-Barr, herpes simplex, parainfluenza, adenovirus, among others. Myalgia may occur in cases of epidemic pleurodynia, known as Bornholm syndrome, caused mainly by enteroviruses. Bornholm syndrome affects the intercostal muscles, resulting in severe intermittent chest pain, fever, sore throat, headache, and myalgia. Furthermore, myalgia can occur in cases of infection with Parechovirus (HPeV), an RNA virus of the Picornaviridae family. HPeV3, in particular, has been linked to infections in children before the age of 5, causing symptoms of myalgia and muscle weakness, mainly affecting the proximal muscles of the legs and arms. This article aims to study the epidemiological and clinical aspects of epidemic myalgia in the last 10 years. Specific objectives include analyzing the epidemiology of the cases, identifying the related etiological agents, describing the clinical presentation and discussing diagnostic and therapeutic approaches. Thus, the method used was that of a systematic literature review, whose objective was to synthesize, in a methodical and impartial way, the available evidence about epidemic myalgia and its respective diagnosis and treatment. Based on results, it was possible to identify that the diagnosis is performed by laboratory tests, such as antibody detection and virus sequencing, which can affect both children and adults, with severe and persistent symptoms, thus, treatment involves the use of analgesics and anti-inflammatories, seeking only to minimize the symptoms.